2023
DOI: 10.1017/eds.2023.11
|View full text |Cite
|
Sign up to set email alerts
|

A novel workflow for streamflow prediction in the presence of missing gauge observations

Abstract: Streamflow predictions are vital for detecting flood and drought events. Such predictions are even more critical to Sub-Saharan African regions that are vulnerable to the increasing frequency and intensity of such events. These regions are sparsely gaged, with few available gaging stations that are often plagued with missing data due to various causes, such as harsh environmental conditions and constrained operational resources. This work presents a novel workflow for predicting streamflow in the presence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Abate et al (2023) also found positive results by using GloFAS hydrological reanalysis and actual evapotranspiration (AET) from Moderate Resolution Imaging Spectroradiometer (MODIS) to calibrate the SWAT model for the ungauged Kobo‐Golina catchment in Ethiopia. Alternatively, hydrological reanalyses can be used to extend existing observational records (Mbuvha et al, 2022) creating a longer record on which to calibrate hydrological models. Care must be taken to ensure that good performance of the hydrological model is expected for the basin of interest and a pre‐processing step may be required before application.…”
Section: Examples Of Applications Of Global Hydrological Reanalysismentioning
confidence: 99%
“…Abate et al (2023) also found positive results by using GloFAS hydrological reanalysis and actual evapotranspiration (AET) from Moderate Resolution Imaging Spectroradiometer (MODIS) to calibrate the SWAT model for the ungauged Kobo‐Golina catchment in Ethiopia. Alternatively, hydrological reanalyses can be used to extend existing observational records (Mbuvha et al, 2022) creating a longer record on which to calibrate hydrological models. Care must be taken to ensure that good performance of the hydrological model is expected for the basin of interest and a pre‐processing step may be required before application.…”
Section: Examples Of Applications Of Global Hydrological Reanalysismentioning
confidence: 99%
“…To predict, a dense neural network layer connects the cell and hidden states to output (y out , Eq. 3) after the input sequence (Mbuvha et al, 2023).…”
Section: E11-6mentioning
confidence: 99%